Influence of Boundary Conditions on Damping Properties of Fluid-Saturatedporous Materials - Kowalski, S.J.; Świderski, T. (Engineering Transactions, 1991)
The object of this paper is the analysis of damping properties of elastic porous media filled with a viscous fluid and, in particular, examination of the influence of boundary conditions and material constants of the medium on the effect of damping. The problem is illustrated by an example of damped vibrations of a fluid-saturated porous cylinder. The attention is concentrated on the analysis of the damping coefficient and the dependence of this coefficient on the boundary conditions and the material constants. The examples analysed show that there exists a broad possibility of controlling this coefficient by a suitable choice of the material constants and the boundary conditions.